2015
DOI: 10.1103/physreva.91.042705
|View full text |Cite
|
Sign up to set email alerts
|

Linear polarization of x-ray transitions due to dielectronic recombination in highly charged ions

Abstract: The linear polarization of x rays produced by dielectronic recombination into highly charged xenon ions was measured at an electron beam ion trap using the Compton polarimetry technique. This opens numerous possibilities for diagnostics of anisotropies of hot plasmas. Moreover, it was observed that the polarization of x rays, following the dielectronic capture populating the [1s2s22p1/2]1 state, is highly sensitive to the Breit interaction. The experimental results for this tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 89 publications
(94 reference statements)
0
22
0
Order By: Relevance
“…DR is sensitive to the Breit interaction [48,69,[81][82][83][84] in both the angular distribution and the linear polarization of the emitted x rays [81]. These properties were measured only for a few resonances in heavy ions [48,50,85,86], and no systematic studies of the alignment in DR, TR or QR were reported.…”
mentioning
confidence: 99%
“…DR is sensitive to the Breit interaction [48,69,[81][82][83][84] in both the angular distribution and the linear polarization of the emitted x rays [81]. These properties were measured only for a few resonances in heavy ions [48,50,85,86], and no systematic studies of the alignment in DR, TR or QR were reported.…”
mentioning
confidence: 99%
“…Recently, the polarization of DR Kα x rays from highly charged Kr and Xe were measured with a novel Compton polarimeter [16,33]. The degree of linear polarization was determined for a few DR resonances and showed agreement with theoretical predictions of a measurable influence of the Breit interaction (BI).…”
Section: Introductionmentioning
confidence: 74%
“…≈ 5.4 eV. Since the degree of linear polarization can be measured quite easily nowadays for a wide range of photon energies by using the techniques of Compton polarimetry [18], such accurate polarization measurements on the γ 2 photons may be used to explore the level-splitting of HCIs.…”
Section: Resultsmentioning
confidence: 99%